A spidroin‐derived solubility tag enables controlled aggregation of a designed amyloid protein. (14th April 2018) - Sarr, Médoune; Kronqvist, Nina; Chen, Gefei; Aleksis, Rihards; Purhonen, Pasi; Hebert, Hans; Jaudzems, Kristaps; Rising, Anna; Johansson, Jan
Abstract : Amyloidogenesis is associated with more than 30 diseases, but the molecular mechanisms involved in cell toxicity and fibril formation remain largely unknown. The inherent tendency of amyloid‐forming proteins to aggregate renders expression, purification, and experimental studies challenging. NT* is a solubility tag derived from a spider silk protein that was recently introduced for the production of several aggregation‐prone peptides and proteins at high yields. Herein, we investigate whether fusion to NT* can prevent amyloid fibril formation and enable controlled aggregation for experimental studies. As an example of an amyloidogenic protein, we chose the de novo ‐designed polypeptide β17. The fusion protein NT*‐β17 was recombinantly expressed in Escherichia coli to produce high amounts of soluble and mostly monomeric protein. Structural analysis showed that β17 is kept in a largely unstructured conformation in fusion with NT*. After proteolytic release, β17 adopts a β‐sheet conformation in a pH‐ and salt‐dependent manner and assembles into amyloid‐like fibrils. The ability of NT* to prevent premature aggregation and to enable structural studies of prefibrillar states may facilitate investigation of proteins involved in amyloid diseases. Abstract : The expression, purification, and experimental studies of amyloid‐forming proteins are challenging due to their inherent tendency to aggregate. We show that NT*, a solubility tag derived from a spider silk protein, controls the aggregation of the amyloid‐forming protein β17 for experimental studies. NT* keeps β17 unstructured whereas calcium or low pH promotes β‐sheet conformation and fibril formation.